Possibilities of landscape design improvements for sacral heritage: Case study: Cathedral ruins garden in Székesfehérvár - Borbás, András; Sárospataki, Máté (4D Journal of Landscape Architecture and Garden Art, 2024)
The Coronation Basilica, with its ruins only visible today, is the emblematic site of Székesfehérvár. The various architectural and environmental development plans and ideas on the cathedral and its surroundings date back along time. Still, since 2023, the thousand-year-old iconic site, which can also be referred to as the sacral centre ofthe Carpathian Basin, has apparently started to gain new momentum. After the troubled fate of one of the cornerstones of Christianity in the Carpathian Basin, it is relevant to open a solid professional debate on the development opportunities. In this publication, with the help of case studies and through an analysis focusing on the current conditions of the site, we identify the the oreticaloptions of three different, but in each case appropriate, strategic directions for the landscape design improvement of the open space and present a specific proposal for renewal and environmental design, which we hope will provide some input for further professional reflection.
Keywords: heritage conservation; landscape design renewal; environmental design; genius loci; ruins site